X=-3x(x+4)

Simple and best practice solution for X=-3x(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X=-3x(x+4) equation:



X=-3X(X+4)
We move all terms to the left:
X-(-3X(X+4))=0
We calculate terms in parentheses: -(-3X(X+4)), so:
-3X(X+4)
We multiply parentheses
-3X^2-12X
Back to the equation:
-(-3X^2-12X)
We get rid of parentheses
3X^2+12X+X=0
We add all the numbers together, and all the variables
3X^2+13X=0
a = 3; b = 13; c = 0;
Δ = b2-4ac
Δ = 132-4·3·0
Δ = 169
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{169}=13$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(13)-13}{2*3}=\frac{-26}{6} =-4+1/3 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(13)+13}{2*3}=\frac{0}{6} =0 $

See similar equations:

| h+4.5=10.8 | | 5/8=w/12 | | x3+-3x+6=0 | | 2.8m=12 | | 5(x+5)-3=5(x-1) | | 7x(2-1)+4=11 | | 18r^2-27r+4=0 | | 4m+3=7-2m | | -1+(-8)+5=x | | 4x^2+96x-144=0 | | 3.2*y=9.6 | | 13x-2x^2=0 | | -6m+40=8(4m+5) | | 6x-20=4x+18 | | 3.6h=- | | 7g+14=10g-55 | | -13x^2+54x+147=0 | | 21+3j=8-3j | | 3+h/6=7 | | -6(-6-8k)=4K-8 | | 17.5=7x+14 | | k/3=3=8 | | n+17=2(3+4) | | 22x+24.50=47x+18.25 | | -3(4x-2)=-12+-6 | | n-(-12)=-3 | | 3.1y-41=3y-17-4.1y | | 12-2m=2m-8 | | 3-4/7x=11 | | 5(x-6)^2=-80 | | XxY=-14 | | 6k=(2k-4) |

Equations solver categories